2020
DOI: 10.1007/s10530-020-02233-5
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring, modeling and harvest management of non-native invasive green iguanas on Grand Cayman, Cayman Islands

Abstract: The green iguana (Iguana iguana) was most likely introduced as a pet and became overabundant during the last 20 years on Grand Cayman. Because negative impacts were unmanageable (e.g., damage to buildings and other infrastructure), a harvest management strategy was developed and implemented, and over 874,252 green iguanas were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
4
13
0
Order By: Relevance
“…Detection probability increased from 2017 to 2019 but was overall low (<0.5) across all years. Nevertheless, detection probability estimates were similar to/higher than those from comparable studies (Bock et al, 2016; Rivera‐Milán and Haakonsson, 2020). However, when an iguana was previously observed, detection probability was equal across years.…”
Section: Discussionsupporting
confidence: 82%
“…Detection probability increased from 2017 to 2019 but was overall low (<0.5) across all years. Nevertheless, detection probability estimates were similar to/higher than those from comparable studies (Bock et al, 2016; Rivera‐Milán and Haakonsson, 2020). However, when an iguana was previously observed, detection probability was equal across years.…”
Section: Discussionsupporting
confidence: 82%
“…Investigation into the 2014 green iguana mortality event was limited to field observation and postmortem examination, and antemortem diagnostics were not performed. In 2019, in conjunction with the Cayman Islands Department of Environment’s green iguana culling program [ 5 ], choanal and cloacal swabs were collected from 15 culled, apparently healthy, free-ranging green iguanas at the QEIIBP. No additional diagnostics were performed in these animals.…”
Section: Methodsmentioning
confidence: 99%
“…Green iguanas were introduced to western Grand Cayman and became evident in the wild in the late 1980s and early 1990s. This species proved to be highly invasive, and by 2017 had reached an estimated population size on Grand Cayman of 1.3 million individuals, distributed island-wide but with highest density in human-modified habitats throughout the island’s western districts [ 5 ]. Due to this overabundance, culling efforts have been underway since October 2018 as a measure to keep the green iguana population under control [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…On Grand Cayman, regular government-supported monitoring efforts revealed that the IAGI population was doubling each year. These data informed annual removal targets that managers used to halt rapid population expansion (Rivera-Mil an & Haakonsson, 2020), while spatial distribution analyses allowed directed response to areas that maximized culling efforts.…”
mentioning
confidence: 99%
“…In response, countries have attempted government‐sanctioned culling campaigns, costing millions of USD, to reduce the abundance of invasive iguanas (Rivera‐Milán & Haakonsson, 2020). For example, since 2018 on the island of Grand Cayman, the government has culled >1.2 million invasive alien Green Iguanas (IAGI) at the cost of 7.2 million USD.…”
mentioning
confidence: 99%